Emotional Maturity in the Ability to Socialize Early Childhood Educators - Nurlia Yusniar (Indonesian Academy of Social and Religious Research (IASRR), 2021)
PAUD teacher must have emotional maturity. The things that are directly related to the emotional maturity level of the teacher are environment, be it at home, the community or the educator's environment in the institution. Therefore, if a PAUD teacher can be well received by his fellow students, he tends to have emotional stability. With the acceptance of teachers in the early childhood environment, it can help students in early childhood development. It is assumed that emotional maturity has a significant relationship with the teacher's ability to socialize. The results showed that most of the PAUD teachers were quite good at emotional maturity, namely 74% of all respondents, then 21% of teachers were in the good category. However, there are still 5% of teachers whose emotional maturity is not good. The level of socialization of early childhood teachers in institutions and the environment is in the quite good category, namely as much as 79%, in the good category, which is 15% and there are still 6% of teachers who have poor social skills. The table shows that there is a relationship between emotional maturity and teacher PAUD socialization in Bunga sub-district, Sragen regency.